Peningkatan Pengetahuan tentang Pengelolaan Scabies pada Santriwati Pondok Pesantren Modern: Increased Knowledge about the Management of Scabies in Female Students of Modern Islamic Boarding School - Romadhon, Yusuf Alam; Kurniati, Yuni Prastyo; Farma, Aufa Faza Fauzan; Yunandar, Rio; Tuanaya, Muhammad Rizqy Noer (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Scabies is a skin disease caused by an infestation of the ectoparasite Sarcoptes scabiei var hominis, which creates tunnels that cause clinical manifestations of itching at night. Health promotion through health hygiene literacy for scabies prevention is essential in various literature. Education is the delivery of health information and an effort to increase motivation/enthusiasm, skills, and confidence in carrying out health actions related to scabies management. According to the author, this comprehensive solution, besides increasing the literacy of individual students and teachers, also increases sustainability in a more comprehensive management of scabies in the future. A total of 60 people, consisting of 56 female students and 4 ustadzah, voluntarily participated in this activity to completion. An indicator of the effectiveness of implementing this activity is improving management knowledge as measured by the participants' pre vs post-test scores. There is a significant average increase in knowledge of scabies management. If we look at the proportion of participants who experienced an increase in their knowledge of scabies management, it was found that 95 percent of the participants had an increase in their knowledge, indicating the effectiveness and sustainability of this educational program. Education that aims to increase knowledge of scabies management as a whole runs effectively and shows the sustainability of this program in the future. These results are expected to increase independence in managing scabies effectively in modern Islamic boarding schools.